1994
DOI: 10.1152/jappl.1994.77.3.1445
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lung liquid secretion in immature fetal sheep: hormonal interaction

Abstract: The present studies were designed to test the hypothesis that arginine vasopressin (AVP) can interact with hydrocortisone and 3,5,3'-triiodothyronine (T3) to induce maturation of lung liquid reabsorptive processes in fetal sheep < 130 days gestation. Lung liquid production rates were measured in chronically catheterized thyroidectomized fetal sheep during eight different experimental treatments. Each experiment consisted of a 2-h control period followed by a 5-h treatment period. Net secretion or reabsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Second, we typically instill at least 50% more blue dextran, which should be sufficient to saturate all binding sites; if all binding sites are saturated with tracer, accurate estimates of lung liquid production can be made since we calculate production rates not from absolute volumes but from relative changes in volume over time. Third, we (unpublished data) and others (11,12) have used both techniques for several years and have consistently found similar estimates of lung liquid production when comparing the two.…”
Section: Discussionsupporting
confidence: 67%
“…Second, we typically instill at least 50% more blue dextran, which should be sufficient to saturate all binding sites; if all binding sites are saturated with tracer, accurate estimates of lung liquid production can be made since we calculate production rates not from absolute volumes but from relative changes in volume over time. Third, we (unpublished data) and others (11,12) have used both techniques for several years and have consistently found similar estimates of lung liquid production when comparing the two.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have suggested that this results from an associated increase in Na + ,K + ‐ATPase expression, as well as an increase in the amiloride‐inhibitable Na + transporter ENaC. Cortisol increases lung liquid reabsoption in response to exogenous arginine vasopressin (AVP) infusion (Cassin et al 1994). However, it is possible that the increase in AQP expression plays an important role in mediating the cortisol‐induced increase in fetal lung secretion as well as the lung's increased ability to reabsorb liquid in response to adrenaline/AVP.…”
Section: Discussionmentioning
confidence: 99%
“…Where the irrecoverable tracer is located proved impossible for us to determine for BD, because we could not demonstrate its presence in blood. Thus the statement that there is no BD measurable in blood in other studies (8,9,17,26) cannot be used as evidence that BD is confined entirely within the lung compartment. For RISA we established that radiolabel was present in fetal blood and a number of fetal and maternal tissues, including the thyroid, after RISA was added to the fetal lung liquid.…”
mentioning
confidence: 89%